and manufacture (He-Ne) laser windows multiplayer antireflection coating - Ghazai , Alaa (University of Thi-Qar Journal of Science, 2008)
In this study;the windows of (He-Ne) laser multilayer antireflectioncoating have been designed from materials MgFas external layer withrefractive index (1.38) and ZnS as internal layer with refractive index (2.35)deposited on BK-7 glass that have refractive index (1.52). Five layers with 2optical path equal quarter wavelength (/4) theoretically and experimentally,and another way, five layers with middle layer (/2) theoretically were used. The all designs are dealing with them in the wavelength less than design ofwavelength with clear difference of the theoretical design with middle layer (/2) at design wavelength. The value of minimum reflectance to one about(0.002) at (680) nm theoretically and (0.0081) at (590)nm while experimentallyabout (0.69) at (650)nm. Another way we obtains on refraction about (0.0040)in a wide range from wavelength (450 - 690)nm when the seven layer withoptical path equal quarter wavelength (/4) theoretically were designed .